Location and Setting of the Mars InSight Lander, Instruments, and Landing Site. Issue 10 (8th October 2020) - Golombek, M.; Williams, N.; Warner, N. H.; Parker, T.; Williams, M. G.; Daubar, I.; Calef, F.; Grant, J.; Bailey, P.; Abarca, H.; Deen, R.; Ruoff, N.; et al.
Abstract: Knowing precisely where a spacecraft lands on Mars is important for understanding the regional and local context, setting, and the offset between the inertial and cartographic frames. For the InSight spacecraft, the payload of geophysical and environmental sensors also particularly benefits from knowing exactly where the instruments are located. A 30 cm/pixel image acquired from orbit after landing clearly resolves the lander and the large circular solar panels. This image was carefully georeferenced to a hierarchically generated and coregistered set of decreasing resolution orthoimages and digital elevation models to the established positive east, planetocentric coordinate system. The lander is located at 4.502384°N, 135.623447°E at an elevation of −2, 613.426 m with respect to the geoid in Elysium Planitia. Instrument locations (and the magnetometer orientation) are derived by transforming from Instrument Deployment Arm, spacecraft mechanical, and site frames into the cartographic frame. A viewshed created from 1.5 m above the lander and the high‐resolution orbital digital elevation model shows the lander is on a shallow regional slope down to the east that reveals crater rims on the east horizon 400 m and 2.4 km away. A slope up to the north limits the horizon to about 50 m away where three rocks and an eolian bedform are visible on the rim of a degraded crater rim. Azimuths to rocks and craters identified in both surface panoramas and high‐resolution orbital images reveal that north in the site frame and the cartographic frame are the same (within 1°). Key Points: A carefully georeferenced high‐resolution image of the InSight lander shows it is located at 4.5024N, 135.6234E in Elysium Planitia, Mars Instrument locations are derived by transforming from spacecraft and site frames into the cartographic frame A viewshed shows the lander is on a shallow regional slope down to the east and a local slope up to the north